KAJIAN AWAL JEJAK PERADABAN DAN ARSITEKTUR MEGALITIK DI KAWASAN UMANG, DATARAN TINGGI GAYO, ACEH - Elysa Wulandari; Chusni Anshori; Asep Yudi Permana; June Ekawati; Masdar Djamaluddin (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2026)
Abstract: The Umang area in the Gayo highlands, Aceh, is a cultural landscape that strongly indicates traces of prehistoric (megalithic) civilization of the Gayo people. This study aims to examine the relationship between geological conditions, landscape elements, and human intervention through the analysis of archaeological features and a landscape architecture approach. The research method was carried out through field observations of site locations, spatial orientation, and symbolic motifs found in the area. The results show a series of archaeological features with a linear structure from the valley to the highlands, consisting of split stone platforms in low elevation areas and slate along the path to the mountains. The slate motifs in the form of various circular patterns indicate symbolic and ritual functions in the area. The absence of traces of permanent habitation, along with the geological conditions of steep slopes and traces of large landslides on the northern side of the area, strengthens the hypothesis that Umang was a ritual site or pilgrimage route, not a residential area. The past community is thought to have been aware of the dangers of natural disasters and created patterns of adaptation to their settlement space. Cosmological understanding is evident in the slate path that climbs from East to West towards the sacred mountain. From a landscape architecture perspective, the lower courtyard functions as a communal space, while the slate path becomes a spiritual transitional space. Keywords: Gayo, Prehistory, landscape archaeology, cosmology, ritual sites. Abstrak: Kawasan Umang di dataran tinggi Gayo, Aceh, merupakan lanskap budaya yang menyimpan indikasi kuat memiliki jejak peradaban pra sejarah (megalitik) masyarakat Gayo. Penelitian ini bertujuan untuk mengkaji hubungan antara kondisi geologis, elemen lansekap, dan intervensi manusia melalui analisis fitur arkeologis serta pendekatan arsitektur lanskap. Metode penelitian dilakukan melalui observasi lapangan terhadap lokasi situs, orientasi ruang, dan motif simbolik yang ditemukan di kawasan tersebut. Hasil penelitian menunjukkan adanya rangkaian fitur arkeologi yang berstruktur pola linear dari lembah menuju dataran tinggi, terdiri atas pelataran batu belah di area elevasi rendah dan batu tulis di sepanjang jalur menuju pegunungan. Motif batu tulis berupa ragam pola melingkar mengindikasikan fungsi simbolik dan ritual pada kawasan tersebut. Tidak ditemukannya jejak hunian permanen, serta kondisi geologi berupa lereng curam dan jejak longsoran besar di sisi utara kawasan, memperkuat hipotesis bahwa Umang merupakan situs ritual atau jalur ziarah (pilgrimage), bukan kawasan permukiman. Masyarakat masa lalu diduga memiliki kesadaran tentang bahaya bencana alam dan mencipatakan pola adaptasi ruang bermukimnya. Tampak pemahaman Kosmologis pada Jalur batu tulis yang mendaki dari Timur ke Barat menuju gunung yang sacral. Dalam perspektif arsitektur lanskap, pelataran bawah berfungsi sebagai ruang komunal, sedangkan jalur batu tulis menjadi ruang transisi spiritual. Kata Kunci: Gayo, pra-sejarah, arkeologi lanskap, kosmologi, situs ritual